Das virtuelle Digitalgebäude Kompendium für Lernende und Lehrende : 2., überarbeitete und erweiterte Auflage - Appenrodt, Jan (2021)
The publication relates to a digital learning system for building construction and building technology. It offers explanations of the didactic concept, technical documents, background information and an extensive collection of exemplary tasks for various target groups and subject areas. The digital 3D model of a two-family house clearly shows essential elements, construction and execution-related relationships and frequently occurring interface problems in buildings. During the virtual tour, constructive and technical building objects can be activated with a mouse click. A context-sensitive menu can be used to activate a wide range of information in different technical depths recall. Comprehensive information, drawings, guidelines, installation instructions and similar documents are provided via a wiki.